At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the value of the expression [tex]\((4x - 12) + \left(\frac{1}{2}xy - 10\right)\)[/tex] for [tex]\(x = 4\)[/tex] and [tex]\(y = 6\)[/tex], let's break down the problem into two main parts and solve each part step by step.
1. Calculate [tex]\(4x - 12\)[/tex]:
a. Substitute [tex]\(x = 4\)[/tex] into the expression [tex]\(4x - 12\)[/tex].
[tex]\(4 \cdot 4 - 12 = 16 - 12 = 4\)[/tex]
So, the value of the first part is [tex]\(4\)[/tex].
2. Calculate [tex]\(\frac{1}{2}xy - 10\)[/tex]:
a. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 6\)[/tex] into the expression [tex]\(\frac{1}{2}xy - 10\)[/tex].
[tex]\(\frac{1}{2} \cdot 4 \cdot 6 = \frac{1}{2} \cdot 24 = 12\)[/tex]
b. Subtract [tex]\(10\)[/tex] from [tex]\(12\)[/tex].
[tex]\(12 - 10 = 2\)[/tex]
So, the value of the second part is [tex]\(2\)[/tex].
3. Add the results from the two parts:
The value of [tex]\((4x - 12) + \left(\frac{1}{2}xy - 10\right)\)[/tex] is given by:
[tex]\(4 + 2 = 6\)[/tex]
Hence, the value of the expression [tex]\((4x - 12) + \left(\frac{1}{2}xy - 10\right)\)[/tex] for [tex]\(x = 4\)[/tex] and [tex]\(y = 6\)[/tex] is [tex]\(6\)[/tex].
1. Calculate [tex]\(4x - 12\)[/tex]:
a. Substitute [tex]\(x = 4\)[/tex] into the expression [tex]\(4x - 12\)[/tex].
[tex]\(4 \cdot 4 - 12 = 16 - 12 = 4\)[/tex]
So, the value of the first part is [tex]\(4\)[/tex].
2. Calculate [tex]\(\frac{1}{2}xy - 10\)[/tex]:
a. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 6\)[/tex] into the expression [tex]\(\frac{1}{2}xy - 10\)[/tex].
[tex]\(\frac{1}{2} \cdot 4 \cdot 6 = \frac{1}{2} \cdot 24 = 12\)[/tex]
b. Subtract [tex]\(10\)[/tex] from [tex]\(12\)[/tex].
[tex]\(12 - 10 = 2\)[/tex]
So, the value of the second part is [tex]\(2\)[/tex].
3. Add the results from the two parts:
The value of [tex]\((4x - 12) + \left(\frac{1}{2}xy - 10\right)\)[/tex] is given by:
[tex]\(4 + 2 = 6\)[/tex]
Hence, the value of the expression [tex]\((4x - 12) + \left(\frac{1}{2}xy - 10\right)\)[/tex] for [tex]\(x = 4\)[/tex] and [tex]\(y = 6\)[/tex] is [tex]\(6\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.